Disseminated avian tuberculosis in captive Ara macao - Sousa, Eliane; Momo, Claudia; Costa, Taiana P.; Pinheiro, Sonia R.; Werther, Karin (My University, 2008)
Avian mycobacteriosis was diagnosed in a captive scarlet macaw (Ara macao) that presented multifocal granulomas on subcutaneous tissue, sciatic nerves, infraorbital sinus, trachea, air sacs, muscles, spleen and liver. Microscopically, central areas of caseous necrosis surrounded by epithelioid macrophage, multinucleated giant cells, and lymphocytes were observed. Acid-fast bacilli were demonstrated by Ziehl-Neelsen stain. Inoculation into Lowenstein-Jensen, Stonebrink and Petragnani media, yielded Mycobacterium spp, which was identified as Mycobacterium avium by polymerase chain reaction technique (PCR).